The atmospherical drought as a decisive factor of yield in the main sour cherry varieties of Hungary - L. Lakatos; T. Szabó; M. Soltész; Z. Szabó; Z. Sun; J. Nyéki (International Journal of Horticultural Science, 2012)
Atmospheric drought causes heavy diffi culties of water supply in most fruit species grown in Hungary, although the modern, intensive plantations are already equipped with irrigation. The use a dripping systems are widely applied, therefore nothing was done to avert the risk of atmospheric drought. In excessively dry seasons the reduction of yields is often due to atmospheric drought. Present study aims to utilise measured data of meteorological parameters (relative air humidity and temperature) to develop an index to characterise drought and measure its effect on fruit yield. Causes influencing yields are multiple. Phytosanitary problems are combined with defi cits of water supply. Water deficit of the soil is avoided by dripping irrigation, but the atmosphere is infl uenced by sprinklers only. Atmospherical drought increases the transpiration of the trees intensely and causes reduction of photosynthetic activity, consequently impairs the yield. Applying the index developed in a plantation of 6 sour cherry varieties grown in Hungary (Meteor, Nefris, Pándy, Újfehértói fürtös, Kántorjánosi, Debreceni bôtermô), we measured the specific yields (yield per volume of tree crown) during the period 1989–2011 using the meteorological database of the growing site. Additionally, other parameters characterising the drought are compared and searched for a method most reliable for judging the specific yielding capacity of sour cherry varieties. The results proved convincingly the utility of the index, especially for the varieties Pándy and Újfehértói fürtös. Comparison with other indices expressing the effects of drought revealed the superiority of our index, which will be applied in the future to express the risk of atmospheric drought.